DOUBLE-REGULATED VERTICAL AXIAL WATER TURBINE - Gale, Janez; Höfler, Edvard; Bergant , Anton; Cizelj, Sandi (Journal of Energy Technology, 2024)
A double-regulated vertical axial water turbine, known as a Saxo turbine, has become a very well-recognised product of the company Litostroj Power, with over 30 commissioned units in the North American market over the previous decade. While this turbine became popular in the North American market due to its compact design, simplified civil construction works, robustness and versatility, this has surprisingly not been the case for the European market, where the Saxo turbine has been overlooked. It seems that European investors prefer and trust more conventional turbines, i.e. classic Kaplan and tubular turbines, instead of the alternative Saxo turbines. This paper examines some of the most important design, hydraulic and economic advantages of Saxo turbines. Special attention is given to a description of the Saxo turbine andits main differences in comparison to tubular and Kaplan turbines. In addition, some of the main issues of hydraulic design and numerical investigations of the flow field in the entire water passage are described. The authors would like to draw the attention of professionals in the field of power generation to this turbine and to initiate discussions that may indicate the concerns of the European investors regarding the Saxo turbine.
Keywords: Hydro power plant; Saxo - vertical axial turbine; Compact and low cost turbine